2021
DOI: 10.1039/d1sc01375k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in single atom catalysts for the electrochemical carbon dioxide reduction reaction

Abstract: The electrochemical carbon dioxide reduction reaction (CO2RR) offers a promising solution to mitigate carbon emission and at the same time generate valuable carbonaceous chemicals/fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(95 citation statements)
references
References 172 publications
1
94
0
Order By: Relevance
“…5,6 Single-atomic catalysts (SACs) have been becoming a research hot spot due to their unique electronic structures of metal atoms coordinated with nonmetal atoms. 7,8 A variety of metal SACs, such as Ni, 9,10 Co, 11 Zn, 12 and Cu, 13−15 have been demonstrated with excellent performances in electrocatalytic CO 2 or CO reduction. Nonetheless, due to the relatively large separation distance between adjacent SAC active sites, the reported selectivities have generally been limited to C 1 products, namely, CO, 16−18 formate, 19,20 methane, 12,15,21 and methanol.…”
mentioning
confidence: 99%
“…5,6 Single-atomic catalysts (SACs) have been becoming a research hot spot due to their unique electronic structures of metal atoms coordinated with nonmetal atoms. 7,8 A variety of metal SACs, such as Ni, 9,10 Co, 11 Zn, 12 and Cu, 13−15 have been demonstrated with excellent performances in electrocatalytic CO 2 or CO reduction. Nonetheless, due to the relatively large separation distance between adjacent SAC active sites, the reported selectivities have generally been limited to C 1 products, namely, CO, 16−18 formate, 19,20 methane, 12,15,21 and methanol.…”
mentioning
confidence: 99%
“…Single‐atom catalysis, a concept proposed by Zhang et al, 11 has been spread in recent years. Single‐atom catalysts (SACs) have been widely studied in various reactions, including organic catalysis, 12–17 environmental catalysis, 18 oxygen reduction reaction, 19–24 water splitting, 25–27 hydrogen oxidation reaction, 28 nitrogen reduction reaction, 29,30 lithium‐sulfur batteries, 31 formic acid oxidation, 32,33 ethanol electro‐oxidation reaction, 34,35 as well as ECR 36–41 . This is mainly because the SACs with unsaturated coordination configurations and maximized metal usage endow them with descent activity and selectivity in those reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) have been widely studied in various reactions, including organic catalysis, [12][13][14][15][16][17] environmental catalysis, 18 oxygen reduction reaction, [19][20][21][22][23][24] water splitting, [25][26][27] hydrogen oxidation reaction, 28 nitrogen reduction reaction, 29,30 lithium-sulfur batteries, 31 formic acid oxidation, 32,33 ethanol electro-oxidation reaction, 34,35 as well as ECR. [36][37][38][39][40][41] This is mainly because the SACs with unsaturated coordination configurations and maximized metal usage endow them with descent activity and selectivity in those reactions. In addition, the relatively homogeneous well-defined active sites in SAC make it a perfect platform for establishing the relationship between the structure of catalyst (electronic structure and coordination structure) and catalytic performance at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous works demonstrated that dispersed Cr, Mn, Fe, Co, Ni, Zn, Pd, Ag, Cd, and Ir SACs prefer reducing CO 2 to CO, and Mo, In, Sn, Sb SACs have been proposed as effective catalysts for FA products. 23,24 Furthermore, they presented an indepth understanding of the structure-activity relationship of SACs and their optimizations in the ECR process. The Faraday efficiency (FE), current density, energy efficiency (EE), cell voltage (CV), and catalytic stability have gradually become satisfactory to meet the demand of industrial ECR for C 1 products.…”
Section: Introductionmentioning
confidence: 99%